If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -8 = 48 Reorder the terms: -8 + 6x = 48 Solving -8 + 6x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 6x = 48 + 8 Combine like terms: -8 + 8 = 0 0 + 6x = 48 + 8 6x = 48 + 8 Combine like terms: 48 + 8 = 56 6x = 56 Divide each side by '6'. x = 9.333333333 Simplifying x = 9.333333333
| 4x+x-8x= | | 3.5p=4 | | 5h+1=3 | | x+3x=120 | | 3x-5x+11x=81 | | 7x+4=5x+7 | | 4t^2+5t-6=0 | | 8x-18=5x | | -10m+300=20 | | 3y-6-2y=6 | | x^2+7x+6=0 | | 3y-52-2y=69 | | .5(x+2)+.75(x+4)=x+5 | | x+0.4x=28 | | 6x-2x+11=-5 | | -2t+5t-9=3(t-4)-5 | | 5-3(2+4)=w-7 | | 2n=0.08 | | 7+5x+2x=14 | | 8x=48 | | 2(a+24)=30 | | 10m=0 | | -z=100 | | 125=4x+6x+5 | | -x+4=-15 | | -x=.51 | | 3x+4+2x=4 | | -3(-c-24)=-3c-24 | | -4x=2 | | -9=9(h-5) | | -(5y+4)-(-4y-8)=-3 | | 36+4u=12 |